YAP1-mediated pancreatic stellate cell activation inhibits pancreatic cancer cell proliferation. (10th October 2019) - Xiao, Ying; Zhang, Hui; Ma, Qiang; Huang, Rui; Lu, Junliang; Liang, Xiaolong; Liu, Xuguang; Zhang, Zhiwen; Yu, Lianyuan; Pang, Junyi; Zhou, Liangrui; Liu, Tonghua; et al.
Abstract: Pancreatic stellate cells (PSCs) are activated in pancreatic ductal adenocarcinoma (PDAC) and are responsible for dense desmoplastic stroma. Yes-associated protein 1 (YAP1) can induce cancer-associated fibroblast activation in liver and breast tumors, but its effect on PSCs is unknown. In the present study, we determined that YAP1 was highly expressed in the nuclei of PDAC-derived activated PSCs. RNAi-mediated or pharmacological inhibition of YAP1 led to PSC deactivation. In addition, YAP1 stimulated the expression of secreted protein acidic and cysteine rich (SPARC) in PSCs, which was inhibited by RUNX1. SPARC secreted from PSCs inhibited pancreatic cancer cell (PCC) proliferation. High expression of nuclear YAP1 in tumor stroma was significantly correlated with SPARC expression and fibrosis degree in human PDAC tissues. Our study revealed a critical role for YAP1 in the regulation of PSC activation and paracrine signaling. Our findings provide insights into a novel rationale for targeting YAP1 to reprogram the PDAC microenvironment. Highlights: PSCs promote pancreatic desmoplasia and have cell-to-cell interaction with PCCs. Inhibition of YAP1 attenuates the activation level of PSCs. YAP1 from PSCs inhibits PCC proliferation via SPARC paracrine.